Male predominance in reported Visceral Leishmaniasis cases: Nature or nurture? A comparison of population-based with health facility-reported data. - Kristien Cloots; Sakib Burza; Paritosh Malaviya; Epco Hasker; Sangeeta Kansal; Guy Mollett; Jaya Chakravarty; Nurpur Roy; Bibek Kumar Lal; Suman Rijal; Shyam Sundar; Marleen Boelaert (Public Library of Science (PLoS), 2020)
Background Bangladesh, India, and Nepal aim for the elimination of Visceral Leishmaniasis (VL), a systemic parasitic infectious disease, as a public health problem by 2020. For decades, male patients have comprised the majority of reported VL cases in this region. By comparing this reported VL sex ratio to the one observed in population-based studies conducted in the Indian subcontinent, we tested the working hypothesis that mainly socio-cultural gender differences in healthcare-seeking behavior explain this gender imbalance. Methodology/principal findings We compared the observed sex ratio of male versus female among all VL cases reported by the health system in Nepal and in the two most endemic states in India with that observed in population-based cohort studies in India and Nepal. Also, we assessed male sex as a potential risk factor for seroprevalence at baseline, seroconversion, and VL incidence in the same population-based data. The male/female ratio among VL cases reported by the health systems was 1.40 (95% CI 1.37-1.43). In the population cohort data, the age- and study site-adjusted male to female risk ratio was 1.27 (95% CI 1.08-1.51). Also, males had a 19% higher chance of being seropositive at baseline in the population surveys (RR 1.19; 95% CI 1.11-1.27), while we observed no significant difference in seroconversion rate between both sexes at the DAT cut-off titer defined as the primary endpoint. Conclusions/significance Our population-based data show that male sex is a risk factor for VL, and not only as a socio-cultural determinant. Biological sex-related differences likely play an important role in the pathogenesis of this disease.